Takotsubo-Like Myocardial Dysfunction Accompanied with Cerebellar Hemorrhage - Akira Tempaku; Tsugiyasu Kanda (Case Reports in Neurological Medicine)
We report a 71-year-old woman with takotsubo-like myocardial dysfunction accompanied with cerebellar hemorrhage. On admission time, although she was unconscious by cerebellar hemorrhage, no obvious heart failure and serological disorder were observed. Three days later, operation for extraventricular drainage was performed. However, conscious level did not change. Four days after admission, the change of electrocardiogram wave pattern and the decrement of heart wall motion were detected. These findings revealed takotsubo-like myocardial dysfunction had occurred. Physical stresses by cerebellar hemorrhage and cranial operation might cause cardiac disorder. This is a remarkable case of takotsubo-like myocardial dysfunction, which is brought about cerebellar hemorrhage against subarachnoid hemorrhage.